Children's Autism Spectrum Diagnostic Techniques Using Machine Learning - Qasim M. Hussein; Zainab .M. Fadhel (Journal of Madenat Alelem University College, 2022)
The number of children diagnosed with autism has increased in recent years. This is due to the inability of doctors to diagnose and treat autism at an early stage, whether through simple traditional or modern methods. To obtain a fast and accurate diagnosis using machine learning techniques with examination methods such as eye appearance, facial patterns, MRI images, movement of body parts and using a combination of eye and brain gaze, the treatment is performed programmatically by creating a system, device, mobile app or robot. Various studies indicate the types of diagnostic methods and which methods are most accurate and reliable.